Effects of fiscal terms and contractual agreements on government take in Nigerian oil industry (2009)
The effects of fiscal terms on true government take under joint petroleum ventures and production sharing contracts were investigated. A generalized cash flow model was developed and used to evaluate government revenues under different fiscal terms and contractual agreements. Analyses revealed that government take is reduced in joint ventures with divestment of equity if other fiscal terms remain unchanged.